2020
DOI: 10.1002/cdq.12238
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Minority Community College Students' Critical Consciousness and Social Cognitive Career Outcomes

Abstract: A need exists to better understand how racial/ethnic minority students' critical consciousness development in response to marginalization may be involved in their educational and career development. We therefore examined the link between critical consciousness development and career decision self‐efficacy and career outcome expectations among racial/ethnic minority community college students. Following social cognitive career theory's conceptual pillars, we developed a testable model integrating critical consc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…Importantly, this study suggests higher critical consciousness may be the result of experiences with gender-based discrimination and oppression that are common amongst Latinas and of the experiences of coming of age in an era of high hostility toward Latinx immigrants (Liang et al, 2017; Siemons et al, 2017). These results are also in line with recent research that has established a link between critical consciousness and college persistence and career development of undocumented Latinxs, U.S.-citizen Latinxs, and minoritized college students more broadly (Cadenas et al, 2018; Cadenas, Lynn, et al, 2020; Cadenas, Cantú, et al, 2020). The present study also supports previous findings that critical consciousness serves as a protective and resilience-building factor among youth who experience oppression and attenuates the negative effects of marginalization (Diemer & Blustein, 2006; Diemer et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Importantly, this study suggests higher critical consciousness may be the result of experiences with gender-based discrimination and oppression that are common amongst Latinas and of the experiences of coming of age in an era of high hostility toward Latinx immigrants (Liang et al, 2017; Siemons et al, 2017). These results are also in line with recent research that has established a link between critical consciousness and college persistence and career development of undocumented Latinxs, U.S.-citizen Latinxs, and minoritized college students more broadly (Cadenas et al, 2018; Cadenas, Lynn, et al, 2020; Cadenas, Cantú, et al, 2020). The present study also supports previous findings that critical consciousness serves as a protective and resilience-building factor among youth who experience oppression and attenuates the negative effects of marginalization (Diemer & Blustein, 2006; Diemer et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…This measure has been linked to measures of low critical consciousness, such as belief in a just world, racial and gender intolerance, and racial prejudice (Neville et al, 2000). In a recent study, this measure was used to assess critical consciousness and was found to be correlated with a measure of activism (i.e., critical action), and predictive of political agency (Cadenas, Lynn, et al, 2020). This measure was chosen over other measures of critical consciousness given its particular focus on racial injustice.…”
Section: Methodsmentioning
confidence: 99%
“…The positioning of these two mediators was conceptualized in our model as serial mediation. We based this positioning on extant research showing a directional and predictive link from critical consciousness to career-related outcomes, including outcome expectations among Latinxs and undocumented immigrants (Cadenas et al, 2018; Cadenas et al, in press; Diemer et al, 2016; McWhirter & McWhirter, 2016). Additionally, the link between discrimination and critical agency was depicted as a positive one, given that critical consciousness is a direct response to marginalization as proposed by critical scholars (Freire, 1972; Jemal, 2017), which is also evidenced among undocumented immigrants (Hernandez, 2018).…”
Section: Conceptual Framework: Serial Mediation Model Of Copingmentioning
confidence: 99%
“…These experiences can be conceptualized as forms of social oppression, which may particularly present barriers for graduate students of modest financial means (Strayhorn, 2010; Wilcox et al, 2019). Prior research has examined the utility of critical consciousness development in supporting socially oppressed students to develop a sense of political agency that enables them to persist against systemic barriers (Cadenas et al, 2018; Cadenas, Lynn, et al, 2020). The current study adopts a model that integrates critical consciousness (CC; Freire, 1973) and social cognitive career theory (SCCT; Lent et al, 1994) to explain the process of CC development among graduate students, and to examine how it may be involved in promoting academic performance and persistence among this increasingly marginalized group.…”
Section: Graduate Studentsmentioning
confidence: 99%
“…Critical reflection refers to marginalized students’ ongoing analyses of oppressive conditions, critical action involves behaviors that confront and resist marginalization (e.g., activism), and political agency refers to students’ perceived abilities to foster positive social change. Research on critical consciousness development suggests that this construct can be quite beneficial in promoting the educational and career progress of marginalized students, including low-income urban youth of color (Diemer & Blustein, 2006; Diemer et al, 2010, 2016), Latinx high school youth (McWhirter & McWhirter, 2016), community college students of color (Cadenas, Cantú, et al, 2020; Cadenas, Lynn, et al, 2020), Latinx college students (Cerezo & McWhirter, 2012), and undocumented immigrants (Cadenas et al, 2018), among others. While some literature has started to address the benefits of critical consciousness development among groups who hold social privileges (Allen & Rossatto, 2009; Watt, 2007),there is limited research on the applicability of critical consciousness to students who simultaneously face privilege and marginalization, such as low-income graduate students in social and behavioral sciences and the humanities.…”
Section: Graduate Studentsmentioning
confidence: 99%